1997
DOI: 10.1111/j.1600-0838.1997.tb00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and pathophysiology of tendon ruptures in sports

Abstract: Of all spontaneous tendon ruptures, complete Achilles tendon tears are most closely associated with sports activities (1–3). Schönbauer (3) reported that 75% of all ruptures of the Achilles tendon are related to sports. In Plecko & Passl (2) the number was 60%. In our material of 430 cases, the number of sports‐related Achilles ruptures was very similar (62%), while only 2% of ruptures of other tendons were sports‐related (P<0.001) (1). Also, the majority of Achilles reruptures occurred in sports. The ruptures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
1
10

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(138 citation statements)
references
References 33 publications
2
125
1
10
Order By: Relevance
“…The largest body of data evaluating the genetic link between tendinopathies, as far as we know, has been reported for patients with Achilles tendinopathy or tearing. Several studies have found a correlation between blood group O or the A/O ratio and Achilles tendon ruptures [23][24][25] . The ABO gene is located on chromosome 9 and encodes for enzymes that produce the major antigens in the ABO blood group system.…”
Section: Discussionmentioning
confidence: 99%
“…The largest body of data evaluating the genetic link between tendinopathies, as far as we know, has been reported for patients with Achilles tendinopathy or tearing. Several studies have found a correlation between blood group O or the A/O ratio and Achilles tendon ruptures [23][24][25] . The ABO gene is located on chromosome 9 and encodes for enzymes that produce the major antigens in the ABO blood group system.…”
Section: Discussionmentioning
confidence: 99%
“…Soft tissue trauma such as tendon and ligament ruptures and joint capsular injuries, which frequently occur, often require a surgical intervention [24,25]. It is presumed that surgical repair combined with the application of biologically active PLG should accelerate healing with an improved outcome.…”
Section: Soft Tissue Healing and Endoscopic Applicationsmentioning
confidence: 99%
“…The abundance of group O was even higher (69%) in individuals who had sustained a re-rupture (Jozsa et al, 1989). Subsequent studies by Kujala and colleagues (Kujala et al, 1992) and Kannus and Natri (Kannus & Natri, 1997 as cited by September, 2007) have documented associations between Achilles tendon rupture and blood group distribution. Interestingly, the relationship between blood group distribution and risk of Achilles tendon rupture was not observed in subsequent work involving 215 Achilles patients recruited in a Finnish cohort (Leppilahti et al, 1996), 78 patients in a Scottish based cohort (Maffulli et al, 2000) and in a small South African based study involving 75 rupture cases and 131 controls as cited by September 2007).…”
Section: Initial Investigationsmentioning
confidence: 88%